If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2(2x + -1) + 3 = 9 Reorder the terms: 2(-1 + 2x) + 3 = 9 (-1 * 2 + 2x * 2) + 3 = 9 (-2 + 4x) + 3 = 9 Reorder the terms: -2 + 3 + 4x = 9 Combine like terms: -2 + 3 = 1 1 + 4x = 9 Solving 1 + 4x = 9 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1' to each side of the equation. 1 + -1 + 4x = 9 + -1 Combine like terms: 1 + -1 = 0 0 + 4x = 9 + -1 4x = 9 + -1 Combine like terms: 9 + -1 = 8 4x = 8 Divide each side by '4'. x = 2 Simplifying x = 2
| 13=k/7 | | 7x-7=13+12 | | -61=d+[-18] | | 3(x+5)+3=3x+8 | | 8x-3=5+4(2x-2) | | 3-5x=10+x | | 4(-6)+10=2(n-7)-6 | | -11-7b=-7(b+2) | | -4(a-3)-(a+6)=1-8a+5+7a | | (3x-4)(2x+11)=0 | | -8+3-6x+6=-7x-2 | | 9x^2-17x-30= | | -8=-2+3/4x | | -3(4y-8)=-36 | | 30+5x+6x=30x | | 2x^4-128x=0 | | 351=3b | | 0.19y+0.05(y+7000)=2030 | | 3(-7a+6)-6a=-2a+18 | | Ax+r=5 | | 325-m=1500+2(m-500) | | 11x+8-30-x=-2(2x+4)-3(2x-2) | | 9y-3=19-24 | | -134=5(1+3x)-4 | | a+x=y+z | | 10-2.7y=y | | 3x-5(x-2)=-6+4x+4 | | 2x^5-6x^4-216x^3=0 | | -2(5x-4)=22 | | x-13=23-2x | | -3(x-2)-1=5(x+3)+38 | | g(x)=-2x+5 |